Video Tutorial Kaligrafi Blackletter - Ainal Husna; Hendra Afriwan (Universitas Negeri Padang, 2021)
The purpose of designing this BlackLetter Calligraphy video tutorial is to provide communicative and informative teaching to the target audience, namely Minang Typers as a community that houses letter artists. Video media was chosen in order to convey information through audio-visual to be effective because it can stimulate two senses simultaneously in conveying information, namely audio (hearing) and audio visual (sight).The method used in designing this video tutorial is a combination of the glass box and black box methods. The glass box and black box methods are inseparable methods because these two methods have their respective portion shapes to form balanced elements in creating or creating a work. The analytical approach uses 5W + 1H. This video tutorial creative design program goes through three stages, namely pre-production, production, and post-production. Keywords: Video, Calligraphy, Blacklette